(untitled) (Studia theodisca, 2014)
Giorgio Vigolo’s lecture Quali musiche suonò Hölderlin? (Which Pieces of Music Did Hölderlin Play?), which the Italian poet held in Rome on April 28th 1966, here edited for the first time, with notes, by Giovanna Cordibella.